Cardiac function in fetal and infants born to mothers with gestational diabetes. (14th October 2021) - Iwashima, S; Yamamoto, Y; Takahashi, K
Abstract: Background: The intraventricular pressure differences (IVPD) IVPD using color M-mode is a specific marker in infants of mothers with gestational diabetes mellitus (GDM). (Circulation R 2019, 378–388). Purpose: This study investigated the myocardial performance of fetuses in mothers with GDM under the new GDM definition. Method: The study population comprised of 27 mothers with GDM and the fetus. Women with GDM were defined as those with a glucose metabolism abnormality that existed before or began during the current pregnancy and was diagnosed using OGTTs. The 5 mothers with type 1 or type 2 DM were receiving insulin before their pregnancy. Fetal echo measurements were performed about median gestational age 35 weeks. The primary outcomes were comparisons of the fetal myocardial performance of GDM with insulin administration and without administration using echocardiography with IVPD, and IVPG. The secondary outcome has investigated the relationships between echocardiography parameters, IVPD, and IVPG, and maternal factors. For all statistical analyses, P<0.05 was considered significant. Result: In the insulin group was higher RV output (Fig. 2A). Maternal max HbA1c was observed to have a positive correlation with fetal RV output, significantly (Fig. 2B). Maternal max fasting blood glucose was observed to have a negative correlation with the Total, Basal and Mid to apical IVPD, significantly, respectively. Serial change of LV Total IVPD from fetal to after birth shown in Slide. In both groups, LV Total IVPD was increasing from fetal and after birth significantly. Conclusion: The mechanism associated with the favorable systolic and diastolic performances in IGDMs is suggested to involve metabolic adaptations in the heart. In diabetic mice, these adaptations seem to prevent the heart from failing during conditions of pressure overload, suggesting a restoration of the balance between glucose and fatty acid utilization is beneficial for cardiac function. In fetal LV and RV-IVPD might be interacted the mother's blood sugar control. These indexes can predict the sensitive fetal and infant's cardiac dysfunction for GDM. Funding Acknowledgement: Type of funding sources: None.